m(m^2-2mn+n)+(m-5n)=m(m-n)^2+(m-5n) 带入m-n=2 得 4m+(m-5n)=5m-5n=5(m-n)=10
已知m-n=2,求代数式m(m^2-2mn+n^2)+(m-5n)的值
1个回答
相关问题
-
已知实数m,n满足mn=3,m+n=5,求代数式m2n+mn2的值
-
已知m2+n2=5,求代数式(2m2+3n2-mn)-(3m2+4n2-mn)的值.
-
已知m2+n2=5,求代数式(2m2+3n2-mn)-(3m2+4n2-mn)的值.
-
已知m²-mn=21.mn-n²=-12求代数式m²-n²与m²-2mn+n²的值
-
已知m²-mn=21,mn-n²=-15,求代数式m²-n²与m²-2mn+n²的值
-
已知m+n=7,mn=-5,求(m-n)(n-m)+(2m-n)+(m-2n)的值.
-
已知m^2-mn=21,mn-n^2=-12,求代数式m^2于n^2与m^2-2mn+n^2的值
-
已知m-n=5,mn=-3,求-(m+4n-mn)-(2mn-2m-3n)+(2n-2m-3mn)的值.
-
已知m-n=5,mn=-3,求-(m+4n-mn)-(2mn-2m-3n)+(2n-2m-3mn)的值